School Principal's Instructional Leadership as a Control Function in the Context of Multicultural Education: Assessment from the Teacher's Perspective - Petrisia Anas Waluwandja; Zummy Anselmus Dami; Paul Arjanto; Arifin Arifin; Agus Maramba Meha (SocioEdu: Sociological Education, 2026)
This research was conducted to explain the understanding of the principal's instructional role from the perspective of control function, which has so far been neglected, even though it is said to be a managerial role of an instructional leader. This research aimed to understand instructional leadership as a control function so that it can be adapted by school principals in Indonesia, who have so far faced challenges in its adaptation in the context of multicultural education. This study uses an ex-post facto research design and a survey. The targeted respondents were teachers (including vice principals, homeroom teachers and teachers), with 337 teachers being sampled using purposive sampling techniques. The analysis technique used in this study is descriptive statistics and independent sample t-test using SPSS software version 25. The results of the study showed that the majority of respondents gave a very high assessment of the role of school principals in various aspects of school management and reflected the effectiveness of school principals in supervision and coaching. In addition, the practice of control functions is often carried out by both public and private schools. Therefore, there are no significant differences in instructional leadership practices in public and private schools.